SAMPAH SEBAGAI BIANG PENYEBAB TERHADAP KEBERSIHAN KOTA SAMARINDA - Futum Hubaib (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2017)
The objective of this research is to kow how to keep Samarinda clean.The location of  it is the city of Samarinda durng the Idul Ftri Party in 2016 .The research is carried out one day after the Feast.The results are (1).The rubbish was spread out in the street and areas which gave bad conditions and existed the illness,(2)The workers of the cleaness took over time but they were not able to do completely,(3).They were not paid salary enough,(4).The local government of Samarinda did not take the experience that every year after Idul Fitri the rubbish is always making problem,(5).The member of parliament , Jasno , from PAN (Nasional Commitment Party) urged to the executive to do the best vwith teh rubbish here.The suggestions are To keep the city here clean , green and healthy always,(2).The workers have to be given enough salary ,(3).The local government of Samarinda has to take the old experience after the feast of Idul Fitry ,(4). Both executive and legislative to give he special attention to the cleaness of the envirement here.